A Comparative Study of Construction Waste Generation Rate Based on Different Construction Methods on Construction Project in Malaysia - Maniam, H.; Nagapan, S.; Abdullah, A. H.; Subramaniam, S.; Sohu, S. (Engineering, Technology & Applied Science Research, 2018)
High construction waste (CW) generation in Malaysia has serious impacts although there are very little available data regarding the relevant issue in Malaysia. This lack of data results in improper CW management and CW disposal without proper control measures. To control the implications of CW, it is very important to understand their quantity which is currently unknown. Past researches in Malaysia, found that CW generation was affected by construction methods (CMs) practiced on site. The aim of this study is to compare the CW generation rate between different CMs for on-going construction projects in Malaysia. Common CMs practiced in Malaysia are conventional construction method (CCM), mixed construction method (MCM) and industrialized building system (IBS). To obtain CW generation data, site visit (SV) method, which consists of direct measurement (DM) and indirect measurement (IM) is applied to this study. CCM was recorded to have the highest amount of waste (197.657 tons). IBS method records 77.188 tons and MCM 53.191 tons. Regarding the average waste generation rate (AWGR), IBS recorded a value of 0.018 tons per square meter, while MCM recorded 0.030 tons per square meter and CCM recorded the highest amount of 0.046 tons per square meter.